Antimicrobial activity of medicinal plants for their potential use in the Brazilian Unified Health System - Vanessa Feitosa Alves; Rebeca Dantas Figueiredo; Yuri Wanderley Cavalcanti; Wilton Wilney Nascimento Padilha (Editorial Ciencias Médicas, 2019)
Introduction: A list of 71 medicinal herbs has been published by the Brazilian Ministry of Health with the purpose of studying and developing medicines obtained from herbs for their potential use in the Unified Health System. Objective: Evaluate the in vitro antimicrobial activity of extracts from medicinal herbs proposed by the Ministry of Health with a view to their possible use in the Unified Health System to combat oral bacteria. Methods: Extracts were obtained from the plants selected in the form of essential oil (Eucalyptus globulus, Mentha piperita and Schinus terebinthifolius) or tincture (Erythrina mulungu, Casearia sylvestris and Maytenus ilicifolia), and were tested against Streptococcus mutans (ATCC 25175), S. oralis (ATCC 10557) and S. salivarius (ATCC 7073). The agar diffusion test was performed by making wells and adding 50 μL of the extracts. After 48 h in a bacteriological incubator, the inhibition haloes were measured with calipers. Minimum inhibitory concentration and minimum bactericidal concentration were determined by microplate microdilution and depletion technique, respectively. The minimum inhibitory concentration corresponded to the lowest dilution, at which there was no visible bacterial growth. The positive control used was 0.12% chlorhexidine. All the tests were performed in triplicate and analyzed descriptively. Results: Maytenus ilicifolia extracts exhibited slightly higher inhibition haloes than the other products. Erythrina mulungu had the lowest minimum inhibitory concentration against S. mutans (2.81 mg/mL) among tinctures, and Mentha piperita (9.00) among essential oils. Erythrina and Mentha piperita extracts were the only two displaying minimum bactericidal concentration against the strains used. Conclusions: The study plant extracts displayed antimicrobial activity against oral microorganisms, particularly against Mentha piperita and Erythrina mulungu.